A guide to the 2006 amendments to the UNCITRAL Model Law on International Commercial Arbitration : legislative history and commentary /: legislative history and commentary. (2015) - Holtzmann, Howard M; Neuhaus, Joseph E; Edda Kristjánsdóttir; Walsh, Thomas W
No abstract available